Multiprofessional assistance in comprehensive support for women affected by spontaneous abortion: a systematic review - Silva, Maria Eduarda Wanderley de Barros (2022)
The present study is a systematic literature review, which consists of broader methodological approaches among literature reviews. Thus, steps were carried out: 1- Elaboration of the guiding question; 2- Sampling of literature; 3-Define the inclusion and exclusion criteria; 4- Develop a research strategy and search the literature; 5-Selection of studies; 6- Assessment of the quality of studies; 7- Data extraction; 8- Synthesis of data and assessment of the quality of evidence and 9- Dissemination of results. The elaboration of a methodological survey for the research was carried out in June 2022, the databases used were the Latin American and Caribbean Health Sciences Literature, Nursing Database and Medical Literature Analysis and Retrieval System Online, using the Descriptors of Health Sciences, namely “Spontaneous Abortion”, “Women's Health” and “Mental Health”. Then, the quantitative of ten articles was selected to compose the corpus of analysis of eligible articles. Thus, it is necessary that a humanized service occurs, with a professional who gives security and offers words of comfort, affection, attention, giving space for the woman to express herself, even to complain. Care is more than an act, it is an attitude, thus, it is necessary for professionals to provide care in a holistic/integral way, without discrimination in relation to the abortion process, regardless of whether it is induced or spontaneous. And for that, it is necessary to understand the importance of holistic care in a subjective way, not in a mechanical way, following only protocols.